‘What makes you think Theology is a subject?’ - Trevor Williams (Journal for the Study of Religion)
This article focuses on a topic, that is captured in a question that Richard Dawkins raised in 1993: ‘What makes you think Theology is a subject?’ My view is that this question is a symptom of how Theology is under attack from many quarters today – from the fearful believers who see it as a threat to their faith, to the secularists who see it as a threat to truth. Foremost among the opponents is Richard Dawkins. Outraged by a donation to Cambridge for the study of theology, he contrasts the usefulness of science with the uselessness of Theology. The question though, is: What is Theology? In this chapter, I draw a distinction between Confessional Theology and Critical Theology. By Confessional Theology I mean the affirmation of an exclusive point of reference by which all other claims to authority and knowledge are judged. Thus Christians ‘confess Jesus Christ is Lord’, and Confessional Theology is the rational articulation of the Christian Faith from within the circle of Faith – the convictions, experiences, and hopes grounded in the story of Jesus and characterized by commitment and involvement. However, there are ways in which both scientists and theologians, and the two types of Theology, can go wrong.